Sustainable Agricultural Production, Organic Farming, Future Opportunities, Trends, Consumption Habits and Priorities - Szőke, Brigitta; Márki, Barbara Éva; Malatyinszki, Szilárd; Dávid, Lóránt Dénes (Journal of Ecohumanism, 2024)
Organic farming has emerged as a cornerstone of sustainable agricultural practices, offering solutions to environmental degradation, biodiversity loss, and soil depletion. This study provides a comprehensive analysis of the role of organic farming in Hungary, exploring its economic, environmental, and social impacts. Using a mixed-methods approach, it examines consumer behavior, sustainability challenges, and opportunities for market expansion. The findings emphasize the potential of integrating circular economy principles to enhance resource efficiency and minimize environmental burdens in agricultural systems. Furthermore, the implications for fostering circular societies and advancing circular tourism are considered, demonstrating the broader significance of sustainable practices in rural development. Special attention is given to Hungarian consumers’ attitudes, highlighting the barriers and opportunities for adopting organic products. This research contributes to the discourse on sustainable development by aligning organic farming with innovative, circular approaches to production and consumption.